A multiscale absorption and transit model for oral delivery of hydroxychloroquine: Pharmacokinetic modeling and intestinal concentration prediction to assess toxicity and drug‐induced damage in healthy subjects - Kannan, Ravishekar; Przekwas, Andrzej (International journal for numerical methods in biomedical engineering, 2020)
Hydroxychloroquine (HCQ) is commonly used in the treatment of malaria and rheumatic diseases. Recently it has also been identified as possible therapeutic option in combating COVID‐19. However, the use of HCQ is known to induce cytotoxicity. In 2020, we developed a multiscale absorption and transit (MAT) toolkit to simulate the dissolution, transport, absorption, distribution, metabolism, and elimination of orally administered drugs in the human GIT at multiple levels. MAT was constructed by integrating the spatially accurate first‐principles driven high‐fidelity drug transport, dissolution, and absorption model in the human stomach and GIT using the recently published Quasi‐3D framework. The computational results showed that MAT was able to match the experimental concentration results better than the traditional compartmental models. In this study, we adapted MAT, to predict the pharmacokinetics of orally delivered HCQ in healthy subjects. The computational results matched the experimental concentration results. The simulated stomach and intestinal fluid and enterocyte concentrations were compared with the in vitro CC50 values. While the peak enterocyte concentrations were several orders lower than the in vitro CC50 values, the peak stomach and the intestinal fluid concentrations were only one order smaller than the in vitro CC50 values. In particular, the peak stomach and the duodenum fluid concentrations were just 3× smaller than the in vitro CC50 values. This implies that the lumen walls are much more susceptible to cytotoxicity‐based damage than the enterocyte layers. We envision that MAT can be used to optimize the dosing regimen of HCQ by maximizing its bioavailability, while simultaneously minimizing the cytotoxic damage. 1. CFD Research Corporation's (CFDRC) multiscale absorption and transit (MAT) toolkit adapted to predict the pharmacokinetics of orally delivered HCQ in healthy subjects.a. First validate for the i.v. delivery.b. Then use for the oral delivery.2. Spatiotemporal concentrations in the stomach and the GIT segments: for the lumen fluids and the enterocytes computed.a. Visualize the spatiotemporal concentration in the lumen fluids and the enterocytes.b. Visually determine the stomach and the particular GIT segments, most vulnerable to the cytotoxic damage.3. Come up with L1 and L∞ metrics to get the probability of the cells dying in the different GIT segments: in the lumen fluids and the enterocytes.a. These metrics are applied in the different stomach and the GIT segments (both enterocytes and the lumen fluids).b. Get the range for the probability of damage.c. We envision that MAT can be used to optimize the dosing regimen of HCQ (and other drugs) by maximize its bioavailability, while simultaneously minimizing the cytotoxic damage.